Conformational effects in protein electrospray‐ionization mass spectrometry. Issue 1 (7th May 2015) - Li, Jinyu; Santambrogio, Carlo; Brocca, Stefania; Rossetti, Giulia; Carloni, Paolo; Grandori, Rita
Abstract : Electrospray‐ionization mass spectrometry (ESI‐MS) is a key tool of structural biology, complementing the information delivered by conventional biochemical and biophysical methods. Yet, the mechanism behind the conformational effects in protein ESI‐MS is an object of debate. Two parameters—solvent‐accessible surface area ( As ) and apparent gas‐phase basicity ( GBapp )—are thought to play a role in controlling the extent of protein ionization during ESI‐MS experiments. This review focuses on recent experimental and theoretical investigations concerning the influence of these parameters on ESI‐MS results and the structural information that can be derived. The available evidence supports a unified model for the ionization mechanism of folded and unfolded proteins. These data indicate that charge‐state distribution (CSD) analysis can provide valuable structural information on normally folded, as well as disordered structures. © 2015 Wiley Periodicals, Inc. Mass Spec Rev 35: 111–122, 2016.